Evaluation Of Medicine Prescription At A Pharmacy In Medan City - Sari, Syilvi Rinda; Rawitri, Kiki; Wahyuni, Sri (Publisher Cv. Inara, 2022)
Pharmacy is a pharmaceutical service facility carried out by pharmacists by providing services directly and responsibly to patients related to pharmaceutical preparations in order to achieve definite results to improve the quality of life of patients. However, currently irrational treatment still often occurs, one of which is with inappropriate prescribing. This will have a negative impact on society. The purpose of this study was to evaluate drug prescribing in one of the pharmacies in the city of Medan. This is a descriptive evaluative research. The data was collected retrospectively and concurrently. Then the raw data was categorized into quantitative data and it was represented in tables to compare the data visually. Meanwhile, qualitative data was collected by observation and interview with the interviewees. The results showed that some indicators of prescribing drugs to patients in one of the pharmacies in Medan city still did not meet the standards, namely the average number of drug items per prescription sheet in 2021 was 3.63 and the percentage of prescribing drugs with generic names in 2021 was 80.9 %. While the prescribing indicators that are in accordance with the standards are the percentage of prescribing antibiotics for 2021 at 6.47%, the percentage of drugs that can be delivered is 90%, and the percentage of drugs that are completely labeled 100%. Based on the results of the study, it was concluded that there were still indicators of prescribing drugs carried out in one of the pharmacies in the city of Medan that did not meet the standards.